2005
DOI: 10.1210/jc.2004-2130
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Endometrial Apoptosis: Randomized Prospective Comparison of Human Chorionic GonadotropinVersusProgesterone Treatment in the Luteal Phase

Abstract: To study control of apoptosis in human endometrium, we examined late luteal-phase endometrial biopsies obtained in the late luteal phase for evidence of apoptosis and compared the effects of exogenous human chorionic gonadotropin (hCG) and progesterone on this process. Using a controlled, prospective, and randomized study design, 12 healthy, fertile, reproductive-age women (ages 20-34 yr) with regular menstrual cycles (range, 26-32 d) were recruited. Each underwent an endometrial biopsy 12 d after a urinary LH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 25 publications
2
34
0
1
Order By: Relevance
“…Apoptosis of endometrial stromal cells can also be reduced by the administration of hCG (45,46). Additionally, hCG messenger RNA (mRNA) is transcribed as early as the two-cell stage of the embryo (47), and the hCG protein is already being secreted by the embryo before implantation (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis of endometrial stromal cells can also be reduced by the administration of hCG (45,46). Additionally, hCG messenger RNA (mRNA) is transcribed as early as the two-cell stage of the embryo (47), and the hCG protein is already being secreted by the embryo before implantation (48,49).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in vivo treatment of women with (h)CG or progesterone significantly increased Bcl-2 in the late luteal phase. Bcl-X levels were higher in the (h)CG treated group compared to the progesterone treated group, while Bax was inhibited by progesterone primarily [59]. Notch1 has also been shown to up regulate the anti-apoptotic protein, Bcl-X L [52], suggesting that it may participate in this effect of (h)CG.…”
Section: Role Of the Cytoskeletonmentioning
confidence: 93%
“…Apoptosis was first described in the human endometrium in 1975 [56] and subsequently shown to be rare in the proliferative endometrium, whereas levels of apoptosis increase in secretory tissue and peaks during the menstrual phase [57,58]. Treatment with (h)CG or progesterone in the midsecretory phase inhibits apoptosis in late secretory phase, implying a role for embryonic signals in inhibiting apoptosis [59].…”
Section: Role Of the Cytoskeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of hCG on endometrium regulation and implantation has been suggested in previous studies (Filicori et al, 2005;Cameo et al, 2006;d'Hauterive et al, 2007). LH administration can increase the LH/hCG receptors during the pre-implantation window and also prevents apoptosis of the endometrial stromal cells (Lovely et al, 2005;Jasinska et al, 2006). Serafini et al (2006) showed that using a low-dose hCG protocol along with a GnRH antagonist treatment in normal ovarian responders avoids premature ovulation, and OHSS.…”
Section: Low Dose Hcg Administration In Conjunction With Gnrh Antagonmentioning
confidence: 99%